Correlation of Lipid Profile and BMI with Fasting Blood Glucose - Seham Eljali; Abdulwahb Al-deib; Mohammed Aljorni; Malek Raghibe (Khalij-Libya Journal of Dental and Medical Research, 2024)
The prevalence in Libya of overweight people has more than tripled from 19.5% in 1984 to 63.5% in 2009, while the rate of obesity has more than doubled over the past three decades leading to a much higher incidence of Type 2 diabetes T2DM. This makes investigation of links between BMI and lipid profiles in Libyan T2DM patients of vital importance. This study was conducted to determine the cor-relation between body mass index (BMI) and lipid profiles in patients with T2DM attending outpatient clinics in the Diabetes and Endocrinology Centre (Ibn Al-Nafees Hospital) Tripoli, Libya. The second objective was to compare BMI, FBS and lipid profiles between T2DM patients and a control group. The study was carried out during the period of June and July 2024 included 122 T2DM patients and 55 healthy subjects. The subject’s serum was analysed for total cholesterol (TC), triglyceride (TG), high density lipoprotein cholesterol (HDL-C) and low-density lipoprotein cholesterol (LDL-C). The possible correlation of BMI with lipid values were analysed. The Pearson’s co-efficient between the BMI and the lipid parameters did not show any significant correlation in T2DM patients. Comparisons of various parameters between T2DM patients and the control group showed that the mean values of fasting glucose levels, weight, BMI, TG, HDL-C and LDL-C were significantly higher in the T2DM group than the control group. There was no correlation found between BMI and lipid profiles in T2DM patients. Type 2 diabetic patients have significantly higher mean weight, BMI, FBS, TG, HDL-C and LDL-C compared with healthy controls لقد تضاعف انتشار الأشخاص الذين يعانون من زيادة الوزن في ليبيا أكثر من ثلاثة أضعاف من 19.5٪ في عام 1984 إلى 63.5٪ في عام 2009، في حين تضاعف معدل السمنة بأكثر من الضعف على مدى العقود الثلاثة الماضية مما أدى إلى ارتفاع معدل الإصابة بمرض السكري من النوع 2 T2DM. وهذا يجعل التحقيق في الروابط بين مؤشر كتلة الجسم وملفات الدهون لدى مرضى السكري من النوع 2 الليبيين ذا أهمية حيوية. أجريت هذه الدراسة لتحديد العلاقة بين مؤشر كتلة الجسم وملفات الدهون لدى مرضى السكري من النوع 2 الذين يرتادون العيادات الخارجية في مركز السكري والغدد الصماء (مستشفى ابن النفيس) طرابلس، ليبيا. وكان الهدف الثاني هو مقارنة مؤشر كتلة الجسم وملفات الدهون بين مرضى السكري من النوع 2 ومجموعة ضابطة. أجريت الدراسة خلال الفترة من يونيو ويوليو 2024 وشملت 122 مريضًا بمرض السكري من النوع 2 و 55 شخصًا سليمًا. تم تحليل مصل المريض من حيث الكوليسترول الكلي (TC) والدهون الثلاثية (TG) وكوليسترول البروتين الدهني عالي الكثافة (HDL-C) وكوليسترول البروتين الدهني منخفض الكثافة (LDL-C). وتم تحليل الارتباط المحتمل بين مؤشر كتلة الجسم وقيم الدهون. ولم يظهر معامل بيرسون بين مؤشر كتلة الجسم ومعايير الدهون أي ارتباط مهم لدى مرضى السكري من النوع 2. وأظهرت المقارنات بين المعايير المختلفة بين مرضى السكري من النوع 2 ومجموعة التحكم أن متوسط ​​قيم مستويات الجلوكوز في الصيام والوزن ومؤشر كتلة الجسم والكوليسترول الكلي والكوليسترول الحميد والكوليسترول الضار كانت أعلى بشكل ملحوظ في مجموعة السكري من النوع 2 مقارنة بالمجموعة الضابطة. ولم يتم العثور على أي ارتباط بين مؤشر كتلة الجسم وملامح الدهون لدى مرضى السكري من النوع 2. ويتمتع مرضى السكري من النوع 2 بمتوسط ​​وزن ومؤشر كتلة الجسم ونسبة الدهون في الدم ونسبة الدهون الثلاثية والكوليسترول الحميد والكوليسترول الضار أعلى بشكل ملحوظ مقارنة بالضوابط الصحي